Changes in the Nitrogenous Compounds during Fermentation of Hilsa Steaks - Majumdar, Ranendra Kumar; Basu, S (Fishery Technology, 2025)
Lona ilish, a traditional salt fermented fish product, made exclusively from hilsa (Tenualosa ilisha), is widely consumed in Bangladesh and adjoining Northeastern parts of India. No detailed scientific studies have been made on lona ilish. To understand the science behind this traditional preservation process, the product was prepared in the laboratory following traditional method, and biochemical changes during fermentation period of 150 days, were studied. At fortnightly intervals, important parameters such as the protein and protein degradation as well as lipid and its degradation in the product were studied. Increase in non-protein nitrogen (NPN), free alpha amino nitrogen (FAN) and total volatile basic nitrogen (TVBN) contents during fermentation indicated hydrolysis of protein. However, the decrease in protein nitrogen content was not significant. A value of NPN/TN of 18% in the fish muscle was found indicative of the fermentation point. High salt content (15.48%), intermediate moisture content (49.89%) and low pH (5.28) of the final product were found to be satisfactory for stability of the lona ilish at ambient temperature.